Preventing Foodborne Illness: Campylobacteriosis - Keith R. Schneider; Renée M. Goodrich; Melissa A. Kirby (EDIS, 2003)
This is one in a series of facts sheets discussing common foodborne pathogens of interest to food handlers, processors and retailers. This document is FSHN032, one of a series of the Food Science and Human Nutrition Department, Florida Cooperative Extension Service, IFAS, University of Florida. Publication: January 2003.